Decidual macrophage subsets and polarization puzzle during the human early pregnancy - Liu, Huiling; Zhang, Liping (Frontiers in Immunology, 2025)
At the maternal-fetal interface from human early pregnancy, decidual macrophages (dMφs) comprise approximately 20% of the leukocyte population, displaying a distinct immunophenotype characterized by hybrid functional features that transcend conventional M1/M2 polarization paradigms. The dynamic balance between M1-like dMφs and M2-like dMφs in human early pregnancy is closely related to the success of pregnancy. However, the comprehensive subsets profiling of dMφs and the factors influencing polarization haven’t been elucidated until recent years. In this review, we first delineate the dMφs compositional proportion and subsets profiling during early gestation. Second, we clarify the mechanisms underlying dMφs recruitment and tissue residency. Finally, we comprehensively synthesize molecular drivers of dMφs polarization and the functional specialization of polarized dMφs in sustaining successful pregnancy. A comprehensive understanding of the molecular network governing dMφs polarization dynamics and their functional contributions to gestational processes will provide crucial insights for developing targeted therapeutic strategies to address pregnancy-related complications.